2020
DOI: 10.1016/j.eats.2019.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Allograft Transplantation With Soft-Tissue Fixation Including the Anterior Intermeniscal Ligament

Abstract: Meniscal allograft transplantation has been introduced as a treatment for symptomatic meniscus-deficient patients to improve clinical outcomes. We describe an arthroscopic technique for meniscal allograft with soft-tissue fixation including the anterior intermeniscal ligament (AIML): arthroscopic double soft-tissue fixation technique. The AIML and anterior and posterior roots are detached and sutured using running locked Krackow stitches. After preparation of the meniscal bed, the meniscus is passed into the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…12 The difference may be due to a higher degree of meniscal extrusion with soft-tissue fixation as compared with bone plug fixation, as reported by Abat et al 13 in 2012. However, we acknowledge that clinical differences between bone plug and soft-tissue fixation have not been proved, and Kim et al 14 suggested that soft-tissue fixation can still be stable and secure enough to limit secondary graft extrusion.…”
Section: Discussionmentioning
confidence: 86%
“…12 The difference may be due to a higher degree of meniscal extrusion with soft-tissue fixation as compared with bone plug fixation, as reported by Abat et al 13 in 2012. However, we acknowledge that clinical differences between bone plug and soft-tissue fixation have not been proved, and Kim et al 14 suggested that soft-tissue fixation can still be stable and secure enough to limit secondary graft extrusion.…”
Section: Discussionmentioning
confidence: 86%
“…Future applications should investigate transosseous suture fixation, bone anchors or bone plug fixation, which seems to be the most efficient fixation method. 25,26 At the 18-month radiographic follow-up, stable fixation of the PSI with evidence of bony incorporation was present. Previous studies in a sheep model using similar implants showed bone-to-implant contact already at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, Kim et al. 24 suggest that MAT with soft tissue is less complex and can still provide stable and secure graft fixation.…”
Section: Discussionmentioning
confidence: 99%
“…According to Abat et al, 23 the suture-only fixation technique also leads to a higher degree of extrusion than bony fixation in MAT. Despite that, Kim et al 24 suggest that MAT with soft tissue is less complex and can still provide stable and secure graft fixation.…”
Section: Discussionmentioning
confidence: 99%